Visuomenės iniciatyva kuriant Lietuvos universitetą - Jurėnienė, Virginija (Lietuvos istorijos studijos, 2002)
On the basis of Lithuanian public initiative and partly, financial support, higher courses were established in Kaunas on January 27, 1920. Higher courses were the very first step in the process of establishment of a higher school in Lithuania.From the beginning of autumn 1920, the Lithuanian society was actively agitating in mass media for the establishment of a university. The most active in this campaign were the lecturers and students of higher courses, teachers, soldiers-students, students, and clericals. The Ministry for Education proposed for the lecturers of higher courses to prepare the project of a Lithuanian university statute. This project was considered in the Ministry for Education only at the beginning of 1921.A massive agitation took place in the press both for a secular as well as for a Catholic university. Politicians began to participate in the agitation for the university in February 1921. This question was raised in Steigiamasis Seimas too. Beginning with the autumn of 1921, when it became clear that only one university could be established, people, public organizations, and the press during meetings were discussing the projects of the statute and submitting resolutions for the government and Seimas. The teachers' trade union, which called a number of city meetings, was the most active.The University of Lithuania was established on February 16, 1922, and it began its function according to the Vilnius University statute accepted by the Soviet of Lithuania on December 5, 1918.The discussions of the statute of the Lithuanian university continued up to the end of March 1922.People and public organizations supported academic youth financially. Until the year of 1921, students were financially supported by clerical organizations. Communities under the titles of "Saulė" and "Rytas" functioned very actively. At the beginning of 1921, a secular community "Žiburėlis" was re-established, the aim of which was to give material help, grants, loans, and dormitories to students.